EKSISTENSI DPR RI SETELAH AMANDEMEN UUD 1945 - W.M. Herry Susilowati (Perspektif, 2006)
After the amendaments of UUD 1945 in 1999, 2000, 2001 and 2002, it is likely that Indonesia Parliament (DPR-RI) has givers bord. It’s existence as an institution that has legislative, budget and control functions as well as interpellation, inquiry and expressing the opinions rights. Therefore, it is strongly expexted to be able to act as national institution that accomodates the people’s aspiration.